2009
DOI: 10.2471/blt.07.050666
|View full text |Cite
|
Sign up to set email alerts
|

Validation of community health workers' assessment of neonatal illness in rural Bangladesh

Abstract: ResearchObjective To estimate the validity (sensitivity, specificity, and positive and negative predictive values) of a clinical algorithm as used by community health workers (CHWs) to detect and classify neonatal illness during routine household visits in rural Bangladesh. Methods CHWs evaluated breastfeeding and symptoms and signs of illness in 395 neonates selected randomly from neonatal illness surveillance during household visits on postnatal days 0, 2, 5 and 8. Neonates classified with very severe diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 16 publications
0
96
0
Order By: Relevance
“…19,20 In this study, LBW was found in 14.1% of patients which is similar to another study conducted in Bangladesh they found LBW 13.3% among their patients. 21 The incidence of LBW was 39.0% in a study conducted in Pakistan, 20.0% in India, and 11.0% in an Ethiopian one. [22][23][24][25] Birth asphyxia accounted for 11.1% of the admissions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In this study, LBW was found in 14.1% of patients which is similar to another study conducted in Bangladesh they found LBW 13.3% among their patients. 21 The incidence of LBW was 39.0% in a study conducted in Pakistan, 20.0% in India, and 11.0% in an Ethiopian one. [22][23][24][25] Birth asphyxia accounted for 11.1% of the admissions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CHWs assessed neonates at home on postnatal days 0, 2, 5 and 8, identified the presence of illness and made referrals to Kumudini Hospital according to a validated clinical algorithm based on the presence of clinical signs and parental reports of symptoms. 7,[15][16][17] For referred neonates, the CHWs facilitated transportation, and all care at the hospital was free. Detailed information on the study design and interventions 15,17 and CHW characteristics 7 is presented elsewhere.…”
Section: Community-based Surveillance Of Neonatal Illnessmentioning
confidence: 99%
“…[2][3][4] In high-mortality settings, serious infections cause up to 50% of neonatal deaths. 5,6 Although infections cause >1000 neonatal deaths every day, 3,7 the causes and patterns of community-acquired neonatal infections have not been adequately investigated in developing countries, where estimates are derived primarily from hospital-based studies, 8,9 even though more than one-half of newborns who die in low-income countries like Bangladesh do so at home. 10 In 2009, we reported the incidence of community-acquired neonatal bacteremia in Bangladesh based on population-based surveillance.…”
mentioning
confidence: 99%
“…Darmstadt [8] refer neonates born at home and requiring specialized treatment. Some of these trained community health workers were so efficient that they could manage sick neonates by themselves.…”
Section: Reviewmentioning
confidence: 99%